The Impact of Digital Challenges On the Development of Startups In the Tourism Sector In Algeria - Narimane Benabderrahmane (SocioEconomic Challenges)
The Algerian government has worked to accelerate digital transformation in recent years, primarily through its orientation towards the knowledge economy and startups, by creating a supportive and framed system and creating many legal frameworks, in addition to taking many incentive measures, which contributed to the development of the startup sector in Algeria, especially tourism startups. However, this sector faces many challenges. This study aims to explore the challenges of the digital transformation of the tourism sector in Algeria through an evaluation research of the challenges of the digital transformation of tourism enterprises in Algeria from the perspective of startup owners. Through qualitative research was conducted through interviews with owners of emerging tourism enterprises to identify the key determinants of digital transformation and critical challenges. Additionally, quantitative research was conducted using a questionnaire to measure these determinants. And quantitative research was conducted by preparing a questionnaire to measure determinants of digital transformation and challenges directed towards owners of startups providing various tourism services, The result of Cronbach's alpha is 0.795 that indicates that the internal reliability of this set is acceptable. The results showed that most startups in the tourism sector were created in 2019 due to establishing the Ministry of Knowledge Economy and Startups in Algeria in the same year. Most tourism startups are located in the North-Central region due to the region's favorable ecosystem. The most critical challenges facing digital transformation in Algeria are the need for more supportive institutions and e-governance. The results also show a correlation between a startup's location and the level of digital transformation challenges. The result indicates that startups located in the High Plateau Center region and the Northeast region face the highest challenges in digital transformation; the results show a correlation between the startup field of activity and the level of digital transformation challenges. The results show that startup activists in direct tourism, e-commerce, and financial services are the most active fields facing higher challenges in digital transformation.